The problem of consciousness in C. G. Jung’s analytical psychology and philosophy of Buddhism: comparative analysis - Maslakova, Katerina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
This article aims at identifying semantic parallels in addressing the problem of consciousness within C. G. Jung’s analytical psychology and the Buddhist tradition. The basis for this consideration can be found in Jung’s works, in which he refers to the problem of consciousness, and in the comment «Abhidharmakosa» to the cosmological doctrine of Buddhism, written by a representative of the Sautrantika Buddhist school. The article refers to the consideration of structural elements of consciousness in Jung’s analytical psychology and philosophy of Buddhism, to the question of the relationship between the concepts of «Ego» in Jung’s works and «Anatman» in Buddhist philosophy, to the idea of «stream» of consciousness and the problem of reality analysis in the frameworks of the two considering approaches. The article also briefly states fundamental differences between the understanding of the problem of consciousness in analytical psychology and Buddhism.
Keywords: Buddhism; analytical psychology; consciousness; C. G. Jung; vaibhasika; sautrantika; Abhidharma; ego